Determinants of adverse birth outcomes among pregnant women in Kintampo municipal hospital, Ghana - Sumaila, Issah; Asumah, Mubarick Nungbaso; Hallidu, Mustapha; Ndekudugu, Abraham; Issifu, Shaibu; Twum, Anthony; Danquah, Collins Boateng; Agodzo, Helen; Appiah, Paulina Clara; Boateng, Fred Adomako (Frontiers in Global Women's Health, 2025)
ObjectiveTo examine the predictors of adverse birth outcomes (ABOs) among pregnant women attending antenatal clinics at the Kintampo Municipal Hospital (KMH) in Ghana.MethodA case-control study was conducted to enrol 408 pregnant women attending antenatal clinic at KMH into the study. Structured questionnaire was used to elicit information from the respondents. Stata version 15 was used to analyse the data. Multiple regression analysis was conducted to determine factors associated with ABOs. Level of statistical significance was established at p < 0.05.ResultsFactors that were significantly associated with ABOs were: receiving of ITN (aOR = 2.03, 95% CI: 1.20, 3.45), at least 8 times visits to ANC (aOR = 0.32, 95%CI: 0.15, 0.69), and partner's education (aOR = 0.53, 95%CI: 0.29, 0.96).ConclusionContrary to expectations, this study revealed that receiving ITNs during pregnancy was associated with ABOs. Further research is needed to explain why receiving ITNs increases the likelihood of ABOs.